Wages and Prices in Relation to International Trade - Taussig, F. W. (Quarterly Journal of Economics, 1906)
Journal Article Wages and Prices in Relation to International Trade Get access F. W. Taussig F. W. Taussig Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 4, August 1906, Pages 497–522, https://doi.org/10.2307/1882719 Published: 01 August 1906